2010
DOI: 10.1007/s00408-010-9260-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical Simulation in Respiratory and Critical Care Medicine

Abstract: Simulation-based medical education has gained tremendous popularity over the past two decades. Driven by the patient safety movement, changes in the educational opportunities available to trainees and the rapidly evolving capabilities of computer technology, simulation-based medical education is now being used across the continuum of medical education. This review provides the reader with a perspective on simulation specific to respiratory and critical care medicine, including an overview of historical and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 66 publications
0
26
0
1
Order By: Relevance
“…The lack of difference between comfort levels in the two arms of the study after intervention was unexpected. The majority of previous randomized simulation studies have found a greater improvement of confidence in the simulation arm when compared to controls [8][9][10][11]. We speculate that the subjects remained somewhat comfortable in both groups because of their limited experience with clinical cases in toxicology.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The lack of difference between comfort levels in the two arms of the study after intervention was unexpected. The majority of previous randomized simulation studies have found a greater improvement of confidence in the simulation arm when compared to controls [8][9][10][11]. We speculate that the subjects remained somewhat comfortable in both groups because of their limited experience with clinical cases in toxicology.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple studies have demonstrated SBME improves subjects' test scores and performance measures when compared to no intervention, but most of these studies lack a control arm of standard educational approaches (i.e., lecture) [8,10]. Furthermore, most previous studies evaluated only knowledge immediately following the intervention [8,10]. We compared the simulation group to a control group who received lecturebased training, and we evaluated knowledge retention 3 months after the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viele Bereiche der Medizin wie Anästhesiologie, Notfallmedizin, Chirurgie, Gastroenterologie, Kardiologie etc. wenden die Simulation zur Ausbildung sowie Evaluation von Ärzten und Pflegepersonal an; hierbei finden verschiedenste Methoden dieser Lehr-, Lern-und Trainingsform Anwendung [8,36,44,45,48,50].…”
Section: Simulationstrainingunclassified
“…The winter curriculum builds on the concepts taught in the summer and devotes time to advanced concepts in the core topic areas. To maximize learning, learners in the summer and winter blocks are taught many of these concepts through simulation and hands-on training (8). Table 3 lists the didactic lectures and the small group and simulation-based learning for the mechanical ventilation and ultrasound sections of the course.…”
Section: Course Development and Evolutionmentioning
confidence: 99%